Seniors' outdoor survey: the environmental audit tool for the elderly attention restoration / Wan Noor Anira Wan Ali @ Yaacob ... [et al.] - Wan Ali, Wan Noor Anira; Mohd Hussain, Nur Huzeima; Mat Nayan, Nadiyanti; Abdullah, Marina; Teh, Mohd Zulhaili (2021)
Seniors' Outdoor Survey (SOS), an environmental audit instrument for determining how much green space in a long-term care environment reflects interests and outdoor usage by the elderly. The content of the leading Seniors' Outdoor Survey (SOS) items initially was based on relevant literature and preliminary studies in a variety of long-term care settings. The restoration needs are vital to the elderly well-being. Overburdening and not getting resources for healing will lead to a health problem that can lead to chronic diseases such as heart disease, exhaustion, insomnia, stress, or burnout syndrome. Therefore, the study aims to evaluate the environmental features (green space) on elderly attention restoration using the Seniors' Outdoor Survey (SOS). The features include (i) fascination, (ii) being away, (iii) extent, and (iv) compatibility components. The relationship of Seniors' Outdoor Survey (SOS) and attention restorative for the elderly are also based on the selected four domains of (i) access to the green space, (ii) outdoor comfort and safety, (iii) outdoor activity and (iv) indoor-outdoor connection at retirement homes. Overall, these findings illustrate the framework for indicating the methodological process which is helpful for future environmental audit assessment in retirement homes in Malaysia. The findings will lead to possible gains for elderly well-being (mental) and quality of life.